Linguistics for legal interpretation - Carney, Terrence R. (UJ Press, 2023)
"Linguistics for Legal Interpretation is a language resource for scholars and practitioners of law who engage and work with statutory interpretation. It draws on lexical semantics, pragmatics and sociolinguistics to both understand and solve language challenges central to the interpretation effort. In addition, this book offers best practice guidelines for dictionary use as well as an introduction to corpus linguistic methods to assist legal interpreters in determining either ordinary or technical meaning."--Publisher website.